Cancer Incidence in Five Continents: Inclusion criteria, highlights from Volume X and the global status of cancer registration. Issue 9 (1st November 2015) - Bray, F.; Ferlay, J.; Laversanne, M.; Brewster, D.H.; Gombe Mbalawa, C.; Kohler, B.; Piñeros, M.; Steliarova‐Foucher, E.; Swaminathan, R.; Antoni, S.; Soerjomataram, I.; Forman, D.
<x xml:space="preserve">Abstract</x> Cancer Incidence in Five Continents (CI5), a longstanding collaboration between the International Agency for Research on Cancer and the International Association of Cancer Registries, serves as a unique source of cancer incidence data from high‐quality population‐based cancer registries around the world. The recent publication of Volume X comprises cancer incidence data from 290 registries covering 424 populations in 68 countries for the registration period 2003–2007. In this article, we assess the status of population‐based cancer registries worldwide, describe the techniques used in CI5 to evaluate their quality and highlight the notable variation in the incidence rates of selected cancers contained within Volume X of CI5. We also discuss the Global Initiative for Cancer Registry Development as an international partnership that aims to reduce the disparities in availability of cancer incidence data for cancer control action, particularly in economically transitioning countries, already experiencing a rapid rise in the number of cancer patients annually.